2011
DOI: 10.1002/j.2334-4822.2011.tb00655.x
|View full text |Cite
|
Sign up to set email alerts
|

12: Academic Dishonesty Among International Students in Higher Education

Abstract: University instructors address and want to eschew student academic misconduct. These educators presume that students understand fully what cheating and plagiarism are. However, the issue of academic dishonesty among international students is complex and difficult. This study investigated the perceptions of international undergraduate and graduate students in a southern U.S. university about possible causes for academic misbehavior. Results reveal several causal variables: previous learning style, English langu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 19 publications
2
19
0
Order By: Relevance
“…Some posit that misconduct is more prevalent among international students faced with university level work in their non-native language. The literature has addressed foreign students at English medium institutions (Arkoudis 2007;Bista 2010Bista , 2011Park 2003). By extension, expatriate instructors and administrators have observed similar trends among students in Western-style universities in countries where English is not the first language.…”
Section: The Academic Integrity Literature and The Gulf Regionmentioning
confidence: 92%
“…Some posit that misconduct is more prevalent among international students faced with university level work in their non-native language. The literature has addressed foreign students at English medium institutions (Arkoudis 2007;Bista 2010Bista , 2011Park 2003). By extension, expatriate instructors and administrators have observed similar trends among students in Western-style universities in countries where English is not the first language.…”
Section: The Academic Integrity Literature and The Gulf Regionmentioning
confidence: 92%
“…Several articles and books (for example Gallant et al ; Hayes and Introna ; Bista ; Carroll ) refer to the special pressures that international students face. As one student puts it: “I have to succeed.…”
Section: Influence On International Students: Intense Pressuresmentioning
confidence: 99%
“…As one student puts it: “I have to succeed. Everyone expects me to succeed and I expect it too” (Bista , 162). Family, extended family, and funding groups are among those who expect success of international students, and often they have made great sacrifices to ensure it.…”
Section: Influence On International Students: Intense Pressuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet plagiarism is a persistent problem in academia, impacting "academic and professional settings globally regardless of size, scope, or mission" (Doss et al, 2016, p. 543). International students, in a strange environment, are burdened already with psychological, social, and academic pressures and hence at a greater risk of not adhering to the strict policy and guidelines of a U.S. academic honor code (Amsberry, 2010;Bista, 2011). In fact, one study found "academic misconduct and plagiarism [were] prevalent among international students" (Bista, 2011, p. 167).…”
mentioning
confidence: 99%